Nepriklausomos Lietuvos Marijampolės marijonų vienuolyno spaustuvė - Jakimavičiūtė, Iveta (Knygotyra, 2003)
Monastic orders and congregations played a very important role in Lithuanian society in 1918–1940. Their main function was to spread and strengthen Catholicism among people. They developed their activities in schools, societies and took an active part in social life as well as in the publishing and distribution of books. The publishing house of Marijampolė Marian Monastery was built in 1926. It also housed the administrative offices of Šaltinis and Šaltinėlis and a library. In the period from 1918–1940 it published 360 books and 6 periodicals: Šaltinis, Šaltinėlis, Spaudos apžvalga, Marijampolės parapija, Šventųjų bendravimas, Artojas. The analysis of the Marian Monastery’s publishing repertoire shows the evolution of their books. Scholarly on religious issues made up the highest part of the Marian’s publications. The diversity of genres is enormous: theological studies, hymnals, moral lectureship and biographies of saints. Some works of fiction were also published. Historical works by Prof. J. Totoraitis in which he analyzed the works of most prominent Lithuanian personalities were especially important not only in the context of the publishing activity of the Marians, but also in the context of Lithuanian history. The Marian monks did not pay enough attention to the typographic quality of their books. The books published by Marian monks reached their readers through libraries, book shops and distributors. The subject matter of this work is the book of Marian monks and the processes related to their publishing. The purpose of the work is to present a detailed analysis of the publishing activities of the Marians, typographic crisis and the repertoire of publications. The work contains four parts as follows: historic features of the Marian Monastery; the printing house of the Marian Monastery in Marijampolė and publishing activities of the Marian monks; analysis of publications including authors’ books, typographic quality, advertising and distribution, and periodicals. There is no doubt that the printing house of the Marian Monastery in Marijampolė and its publications played an important role in the development both of religious and lay publications and periodicals during the period of Lithuanian independence.